Surface Uplift and Topographic Rejuvenation of a Tectonically Inactive Range: Insights From the Anti‐Atlas and the Siroua Massif (Morocco) - Clementucci, R.; Ballato, P.; Siame, L.; Fox, M.; Lanari, R.; Sembroni, A.; Faccenna, C.; Yaaqoub, A.; Essaifi, A. (Tectonics (Washington, D.C.), 2023)
The Atlas‐Meseta intracontinental orographic system of Morocco experienced recent, large‐scale surface uplift as documented by elevated late Miocene, shallow‐water marine deposits exposed in the Middle Atlas Mountains. The Anti‐Atlas Mountains do not present any stratigraphic records that document regional vertical movements, however, the presence of a high‐standing, erosional surface, and the transient state of the river network, provides insights into the uplift history of the belt and the mechanisms that drove it. Here, we combine geomorphic and stream profiles analyses, celerity of knickpoints and linear inverse landscape modeling with available geological evidence, to decipher the spatial and temporal variations of surface uplift in the Anti‐Atlas and the Siroua Massif. Our results highlight the presence of a transient landscape and document a long wave‐length topographic swell (∼100 × 600 km) with a maximum surface uplift of ∼1,500 m in the Siroua Massif and ∼1,100 m in the central Anti‐Atlas most likely starting from ∼14 to 10 Ma. Surface uplift occurred in association with the onset of late Miocene magmatism in the Siroua and Saghro Massif and contractional deformation in the High Atlas. Regional surface uplift was most likely due to deep‐seated mechanism, such as asthenospheric upwelling. Additional processes such as magma injection and faulting contributed to the surface uplift of the Siroua Massif. Overall, our approach allows to quantitatively constrain the transient state of the landscape and the contribution of regional surface uplift on mountain building processes. Key Points The transient state of the stream network and the high‐standing erosional surface document a recent phase of topographic rejuvenation Uplift started at ∼14–10 Ma and increases from the western (0.5 km) to the central Anti‐Atlas (1.1 km) and the Siroua Massif (1.5 km) Regional surface uplift is most likely due to astenospheric upwelling, locally combined (Siroua Massif) with magma injection and faulting